The Ecology of Zaprionus Genus in Brazil and Adaptation Process during The Bioinvasion - Galego, Luis Gustavo da Conceicao (Universitas Muhammadiyah Surakarta, 2023)
The Ecology of Zaprionus Genus in Brazil and Adaptation Process during The Bioinvasion